2022
DOI: 10.1021/acsami.1c23014
|View full text |Cite
|
Sign up to set email alerts
|

A Superior and Stable Electrocatalytic Oxygen Evolution Reaction by One-Dimensional FeCoP Colloidal Nanostructures

Abstract: Transition metal phosphides (TMPs) are expected to be excellent electrocatalysts for oxygen evolution reaction (OER) because of their high stability, highly conducting metalloid nature, highly abundant constituting elements, and the ability to act as a precatalyst due to in situ surface-formed oxy-hydroxide species. Herein, a "one-pot" colloidal approach has been used to develop a rod-shaped one-dimensional non-noble metal FeCoP electrocatalyst, which exhibits an excellent OER activity with an exceptionally hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 62 publications
2
32
0
Order By: Relevance
“…The deconvoluted spectra of Cu 2p in Figure f indicate the existence of only Cu 0 where Cu 2p 3/2 , 932.68 eV and Cu 2p 1/2 , 952.03 eV with Δ = 19.35 eV were assigned for Cu 0 . However, the deconvoluted XPS spectrum of Co 2p suggested that the cobalt was present in the elemental as well as in the oxidized form (Figure g). , The Co 0 is confirmed from the peaks at 778.56 eV (Co 2p 3/2 ) and 793.81 eV (Co 2p 1/2 ). The XPS peaks observed at 781.55 and 797.35 eV correspond to Co 2p 3/2 and Co 2p 1/2 , respectively, with a spin–orbit splitting of 15.80 eV, and two shakeup satellite peaks (785.78 and 803.07 eV) indicate the existence of Co 2+ /Co 3+ .…”
Section: Results and Discussionmentioning
confidence: 94%
“…The deconvoluted spectra of Cu 2p in Figure f indicate the existence of only Cu 0 where Cu 2p 3/2 , 932.68 eV and Cu 2p 1/2 , 952.03 eV with Δ = 19.35 eV were assigned for Cu 0 . However, the deconvoluted XPS spectrum of Co 2p suggested that the cobalt was present in the elemental as well as in the oxidized form (Figure g). , The Co 0 is confirmed from the peaks at 778.56 eV (Co 2p 3/2 ) and 793.81 eV (Co 2p 1/2 ). The XPS peaks observed at 781.55 and 797.35 eV correspond to Co 2p 3/2 and Co 2p 1/2 , respectively, with a spin–orbit splitting of 15.80 eV, and two shakeup satellite peaks (785.78 and 803.07 eV) indicate the existence of Co 2+ /Co 3+ .…”
Section: Results and Discussionmentioning
confidence: 94%
“…Further, the inset of Figure a shows the XRD pattern of as-prepared NCP nanocrystals where all the peaks resemble the standard Ni 2 P XRD pattern (JCPDS 71-2336) revealing a pure single-phase and crystalline form of NiCoP nanoparticles. , For the control experiments, the XRD patterns of Pt, FCP, Ni 2 P, and CoP NPs were also recorded and found to be in a pure phase (Figure S1). , The transmission-electron microscopy (TEM) images in Figure b and Figure S2a,b clearly exhibit the typical hollow ring morphology of the ZCM sample with an average size of ∼500 nm. These large sized novel hollow rings are formed from the self-assembly of the small sized hollow particles (nanoscale building blocks) with an average size ∼115 nm as shown in Figure c.…”
Section: Resultsmentioning
confidence: 99%
“…The individual Fe (oxy)hydroxide and Co (oxy)hydroxide species or FeCo (oxy)hydroxide species have been commonly considered as active OER sites in an alkaline medium. 62–64 Now, taking into account the Tafel slope of the alkaline OER of FCP (47 mV dec −1 ), either [M* + OH − → M–*OH + e − ] or [M–*OOH + OH − → M* + O 2 + H 2 O + e − ] could be the rate-determining step (RDS) in the electron transfer reactions. 61,65 Recent theoretical calculations by Shinagawa et al pointed out that a low OER Tafel slope indicates a high coverage of M–*OH (>0.6), similar to that of the HER.…”
Section: Resultsmentioning
confidence: 99%
“…[62][63][64] Now, taking into account the Tafel slope of the alkaline OER of FCP (47 mV dec−1 ), either [M* + OH − / M-*OH + e − ] or [M-*OOH + OH − / M* + O 2 + H 2 O + e − ] could be the rate-determining step (RDS) in the electron transfer reactions. 61,65 Recent theoretical calculations by Shinagawa et al pointed out that a low OER Tafel slope indicates a high coverage of M-*OH (>0.6…”
mentioning
confidence: 99%